Redução de fagulhamento em máquinas automáticas de solda ponto em indústria automotiva - Dolcinotti, George Lucas [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This dissertation presents a project to reduce splash in automatic spot welding machines in a multinational automotive vehicle industry. Many problems have been caused by the large amount of splash coming from the soldering point. The main one is the accumulation of dirt in the welding equipments, causing a time of inactivity in the machines, dimensional deviations, quality problems, among others. There is a great cost with specialized cleaning staff for the welding sites and surrounding areas. In addition, there is an extra labor cost of corrective and emergency maintenance, especially on staples and soldering tweezers of a cell. The spot weld is basically a type of electric current welding. The joining of two parts in the welding by electrical resistance is done through the generation of heat, due to the passage of electric current and the application of pressure between the parts. During the process the parts heat up and the melting occurs at the point of contact on the separation surface. The resistance-point soldering process is divided into four stages, with four different times: compression time, where the machine closes and presses the plates (without the passage of current); weld time, where the current is tripped and the melt occurs; retention time, where the solder is completed and the gripper keeps closed for solder cooling; and pause time, where the machine is released and can move to the next point. In addition to these basic factors (specific times, current and force), there are others that strongly influence the quality of welding and consequently the degree of sparking. A spot weld should have its electrodes aligned, with equal diameters and well cooled during and after welding. Another factor of great influence is the compression time. This is the time between the application of force and the passage of the current. It is necessary to allow the soldering head to adjust before... (Complete abstract click electronic access below)

Este trabalho apresenta um projeto para redução de fagulhamento em máquinas automáticas de solda ponto em uma indústria multinacional de veículos automotores. Muitos problemas têm sido causados pela grande quantidade de fagulhas provenientes da solda ponto. O principal é o acúmulo de sujeira nos equipamentos de solda, causando um tempo de inatividade nas máquinas, desvios dimensionais, problemas de qualidade, entre outros. Há um grande custo com equipe de limpeza especializada para os locais de solda e adjacências. Além disso, há um custo extra com mão de obra de manutenções corretivas e emergenciais, principalmente em grampos e pinças de solda de uma célula. A solda ponto é basicamente um tipo de soldagem por corrente elétrica. A junção de duas peças na soldagem por resistência elétrica é feita através da geração de calor, devido à passagem de corrente elétrica e da aplicação de pressão entre as peças. Durante o processo as peças aquecem e ocorre a fusão localizada no ponto de contato, na superfície de separação entre ambas. O processo de solda ponto por resistência é dividido em quatro estágios, com quatro diferentes tempos: tempo de compressão, onde a máquina fecha e pressiona as chapas (sem a passagem de corrente); tempo de solda, onde a corrente é disparada e ocorre a fusão; tempo de retenção, onde a solda é concluída e a pinça mantém fechada para o resfriamento da solda; e tempo de pausa, onde a máquina fica liberada, podendo passar para o ponto seguinte. Além desses fatores básicos, tempos específicos, corrente e força, tem-se outros que influenciam fortemente na qualidade de solda e consequentemente no grau de fagulhamento. Uma solda ponto deve ter seus eletrodos alinhados, com diâmetros iguais e bem refrigerados durante e após a solda. O tempo de... (Resumo completo, clicar acesso eletrônico abaixo)
Sparkle reduction in automated spot welding machines in the automotive industry
Keywords: Soldagem elétrica; Correntes eletricas; Solda e soldagem; Eletrodos; Electric welding